Analysis on influence factors of back pressure in an asymmetrical algebraic scroll compressor. (June 2022) - Wang, Che; Zhang, Shuai; Lei, Bowen; Cheng, Junming; Wu, Jianhua
Abstract: The back-pressure mechanism plays an important role in the performance and efficiency of the scroll compressor. In this work, the level of back pressure of an asymmetrical algebraic scroll compressor is experimentally measured and it is shown that the back pressure decreases with the increase of compressor frequency under all tested operating conditions. The mathematical model of the scroll compressor is also developed in order to further investigate other influence factors of back pressure. The predicted back pressure is compared with experiment result, showing a similar trend to them. The pressures in each working chamber and back-pressure chamber are studied to identify the effect of leakage through flank and radial leakage gaps. The influences of compressor frequency, leakage gap size, back-pressure volume on back pressure are discussed in detail based on developed model. The axial forces and stability of the orbiting scroll are also evaluated under these operating conditions by using interpolation method to calculate the pressure distribution on tips.